Enhanced gold recovery from mine tailings using continuous stirred tank reactor (CSTR) - 463596 Mior Ahmad Khushairi Mohd. Zahari; Wan Azlina Ahmad, supervisor; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Master of Science (Chemistry)) - Universiti Teknologi Malaysia, 2002